Students’ Voice of Digital Literacy in Learning English - Silvia Nanda Putri Erito (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2022)
Digital literacy competence played an essential role in the growth of University students to achieve their goals of learning. This study was carried out to define the students’ perception of the use of digital literacy in learning English. The participant consists of the students of the Accounting and Information system program, at Bina Sarana Informatika University. 50 students were chosen by purposive sampling technique. The students had a distinctive response regarding the use of digital literacy competence and how they perceive it. This study was a qualitative case study. The data was gathered through open-ended questionnaires and classroom observation. The findings showed that the students had a positive voice regarding the use of digital literacy competence in learning English, they argued that digital literacy need willingness and critical thinking skills.